On the nature of the plant ER exit sites - McGinness, Alastair J.; Schoberer, Jennifer; Pain, Charlotte; Brandizzi, Federica; Kriechbaumer, Verena (Frontiers in Plant Science, 2022)
In plants, the endoplasmic reticulum (ER) and Golgi bodies are not only in close proximity, but are also physically linked. This unique organization raises questions about the nature of the transport vectors carrying cargo between the two organelles. Same as in metazoan and yeast cells, it was suggested that cargo is transported from the ER to Golgi cisternae via COPII-coated vesicles produced at ribosome-free ER exit sites (ERES). Recent developments in mammalian cell research suggest, though, that COPII helps to select secretory cargo, but does not coat the carriers leaving the ER. Furthermore, it was shown that mammalian ERES expand into a tubular network containing secretory cargo, but no COPII components. Because of the close association of the ER and Golgi bodies in plant cells, it was previously proposed that ERES and the Golgi comprise a secretory unit that travels over or with a motile ER membrane. In this study, we aimed to explore the nature of ERES in plant cells and took advantage of high-resolution confocal microscopy and imaged ERES labelled with canonical markers (Sar1a, Sec16, Sec24). We found that ERES are dynamically connected to Golgi bodies and most likely represent pre-cis-Golgi cisternae. Furthermore, we showed fine tubular connections from the ER to Golgi compartments (ERGo tubules) as well as fine protrusions from ERES/Golgi cisternae connecting with the ER. We suggest that these tubules observed between the ER and Golgi as well as between the ER and ERES are involved in stabilising the physical connection between ER and ERES/Golgi cisternae, but may also be involved in cargo transport from the ER to Golgi bodies.